PERLINDUNGAN HUKUM TERHADAP PEJUANG LINGKUNGAN HIDUP YANG DIJAMIN DALAM UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP - Tundjung Herning Sitabuana; Harry Setiawan (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Environment is definitely one of the most important things that we as human beings need because we are actually just a small part of it. Criminalization of environmental activists is pretty common in Indonesia which is a serious problem for the state to protect human rights. The protection of environmental activists has been regulated in the environmental law, but that doesn’t really protect the activists from the courtroom. Undang-Undang No. 32 Tahun 2009 or Law Number 32 Year 2009 is the law that regulates the environment and it also regulates the protection of the environmental activists as written in the Article 66, but that doesn’t stop the fact that many activists had to deal with the authorities just because they tried to protect one of their human rights which is the healthy environment. This is such a problem that the government and the lawmakers have to fix. The Anti SLAPP idea is one of the keys to protect environmental activists from being criminalized. This research is using normative approach.